Juozo Gurauskio laiškai - Kuzmickas, Vincas (Literatūra, 1969)
19 letters of the Lithuanian writer J. Gurauskis (1884-1911) are presented here. They are addressed to Lithuanian writers - J. Tumas-Vaižgantas (13 letters), G. Petkevičaitė-Bitė (2 letters) and editors of the Lithuanian newspapers: „Vilniaus žinios“ („The News of Vilnius“), „Lietuvos žinios“ („The News of Lithuania“), „Viltis“ („The Hope“). All the letters were written in the last years of the writer's life (1908-11) spent in Kiev, Jalta and Agudzera (Abkhazia). The letters present a valuable material for one studying the creative life and aesthetic views of J. Gurauskis, as well as the whole cultural and literary life of Lithuania at the beginning of the 20th century.When reading the letters besides of the names of the Lithuanian men of culture one can find several figures of the Ukrainian cultural life (O. Pčilka - L. Ukrainka's mother, composer N. Lysenko, etc.), the closest writer's friend and coeval - the Russian engineer I. V. Kashkarov and others mentioned.